Migration to European lands stood the test of time or when the humanist discourse taught to Europeans came to shox ils emptiness. - MAACHE, Youcef; GAHAR, Sabrina GAHAR2 (Journal of Human Sciences, 2021)
Migrating supposes a journey, a displacement under duress, a flight, a quest, an aspiration, a hope… The journey undertaken sometimes in a hurry without any preparation and often without money has a price which is necessary, year in year out, pay and one never fulfills such a condition without leaving a lot of oneself in it, without eminently social, identity and cultural sacrifices. What about its facts, effects and day-to-day materiality, at a time of the rise of proven xenophobia and the "profusion" of populist leaders who continue to excel in the multiplication of diatribes against all forms? Of “uncontrolled” migration? We will make, below, a point of honor to make and to highlight the paradoxes of the teaching of the “humanities” and especially of the humanist philosophy of the countries qualified as “host countries” by questioning some European intellectuals we met during a seminar on interculturality.